2023
DOI: 10.1038/s41467-023-38813-x
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytically impaired Drosophila glial cells fuel neural metabolism via β-oxidation

Abstract: Neuronal function is highly energy demanding and thus requires efficient and constant metabolite delivery by glia. Drosophila glia are highly glycolytic and provide lactate to fuel neuronal metabolism. Flies are able to survive for several weeks in the absence of glial glycolysis. Here, we study how Drosophila glial cells maintain sufficient nutrient supply to neurons under conditions of impaired glycolysis. We show that glycolytically impaired glia rely on mitochondrial fatty acid breakdown and ketone body pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Recent research has demonstrated that fatty acid oxidation in adult mouse astrocytes is crucial for cognitive function 74 . In Drosophila, glial cells provide energy to neurons through ketogenesis, which is necessary for memory and survival during periods of starvation or when glial glycolysis is absent 75,76 . Further studies are necessary to investigate the role of ketogenesis in the mammalian brain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that fatty acid oxidation in adult mouse astrocytes is crucial for cognitive function 74 . In Drosophila, glial cells provide energy to neurons through ketogenesis, which is necessary for memory and survival during periods of starvation or when glial glycolysis is absent 75,76 . Further studies are necessary to investigate the role of ketogenesis in the mammalian brain.…”
Section: Discussionmentioning
confidence: 99%
“…The concurrent mitochondrial dyshomeostasis and slow pyruvate consumption, resulted from loss of tty, implicate that mitochondrial respiration contributes to ATP production in glia. Indeed, recent studies have shown that mitochondrial fatty acid breakdown and OXPHOS also support glial functions (Chen et al, 2022;McMullen et al, 2023;Mi et al, 2023;Rose et al, 2020;Zehnder et al, 2021). While both glycolysis and OXPHOS may contribute to glial bioenergetics, energyexpensive processes, such as glutamate uptake (Danbolt, 2001;Sibson et al, 1998), might demand accelerated ATP production in glia.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the glycolytic inhibitor 2DG also expedited the recovery of TPP and neuronal excitability similar to glucose, we speculate 2DG-animals may have switched to β-oxidation to fuel recovery ( McMullen et al, 2023 ). Fatty acids metabolism is slower but generates greater energy compared with glycolysis, which may explain the initial low CO 2 output in 2DG group.…”
Section: Discussionmentioning
confidence: 99%
“…Although insect CNS stores little lipids, glial cells may mobilize peripheral fat body reserves when glycolysis is impaired, and supply ketone bodies to neurons as oxidative fuel ( Rittschof and Schirmeier, 2018 ). For instance, it is thought that Drosophila glia secretes Glaz (homologous to apolipoprotein ApoD) to communicate with the fat body during starvation ( McMullen et al, 2023 ); a similar mechanism likely exists in the locust CNS, considering the central role of fatty acids in powering flight muscles ( Haunerland, 1997 ). In the context of anoxic SD recovery, glycolysis block coupled with increased β oxidation may help prevent the oversupply of TCA cycle substrates and preserve the stoichiometric balance of intermediates.…”
Section: Discussionmentioning
confidence: 99%